Customers' perception towards cellular mobile telephone operators - Rahman, Muhammad Sabbir; Haque, A. K. M. Ahasanul; Sayyed Ahmad, Mohd. Ismail (ORIC Publication, 2013)
This research was designed to address the research problems regarding the significant factors that affect perception of customer s in the choice of an operator line, and also those factors significantly affecting the consumers’perceptions